Deciphering the quality of SARS‐CoV‐2 specific T‐cell response associated with disease severity, immune memory and heterologous response. Issue 4 (12th April 2022) - Pérez‐Gómez, Alberto; Gasca‐Capote, Carmen; Vitallé, Joana; Ostos, Francisco J.; Serna‐Gallego, Ana; Trujillo‐Rodríguez, María; Muñoz‐Muela, Esperanza; Giráldez‐Pérez, Teresa; Praena‐Segovia, Julia; Navarro‐Amuedo, María D.; Paniagua‐García, María; García‐Gutiérrez, Manuel; et al.
Abstract: SARS‐CoV‐2 specific T‐cell response has been associated with disease severity, immune memory and heterologous response to endemic coronaviruses. However, an integrative approach combining a comprehensive analysis of the quality of SARS‐CoV‐2 specific T‐cell response with antibody levels in these three scenarios is needed. In the present study, we found that, in acute infection, while mild disease was associated with high T‐cell polyfunctionality biased to IL‐2 production and inversely correlated with anti‐S IgG levels, combinations only including IFN‐γ with the absence of perforin production predominated in severe disease. Seven months after infection, both non‐hospitalised and previously hospitalised patients presented robust anti‐S IgG levels and SARS‐CoV‐2 specific T‐cell response. In addition, only previously hospitalised patients showed a T‐cell exhaustion profile. Finally, combinations including IL‐2 in response to S protein of endemic coronaviruses were the ones associated with SARS‐CoV‐2 S‐specific T‐cell response in pre‐COVID‐19 healthy donors' samples. These results could have implications for protective immunity against SARS‐CoV‐2 and recurrent COVID‐19 and may help for the design of new prototypes and boosting vaccine strategies. Abstract : "In acute infection, combinations with only IFN‐γ were deleterious and those with IL‐2 were associated with a better course of acute infection. Additionally, mild patients had a more polyfunctional T response. In severe patients, there was increased antibody production inversely associated with the expression of combinations including IL‐2. Seven months after infection, cellular and humoral responses were present, with T‐cell response quality similar to acute infection. However, previously hospitalised subjects had higher T‐cell exhaustion. Finally, an association was found between the response to HCoV and SARS‐CoV‐2 mainly mediated by IL‐2 expression in pre‐COVID‐19 participants."